Implementasi Hotspot Sebagai Iklan Menggunakan Mikrotik di Moeslem Tronik - Wahid, Zainul; Diansyah, Tengku Moh; Suriati, Suriati (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2022)
The function of advertising as an medium has been widely used, wich one kind of them it used the hotspot login display, because the display hotspot login basicly in HTML, it can be adapted to the login page admin wishes. Generally, the use hotspot using the mikrotik, it can be more flexible in managing the network. The function of this hotspot isn't only using wifi, but are connected by using wires also can use the hotspot system. The implementation of this hotspot who used as advertising and internet regulated the employer staff, and distributed to customers. Hotspots function is to limit the time of internet based on user login and regulate the speed of the internet